Laparoscopic gastric plication: towards standardization - Monem Ibrahim, Ahmed Abdel; Elgeidie, Ahmed; Gadelhak, Nabil (International Surgery Journal, 2017)
Background: Laparoscopic gastric plication (LGP) is a restrictive bariatric procedure which was found to be safe, effective and economic as well. However, it hasn’t a good reputation among some bariatric surgeons due to some reasons; the most important of them is lack of standardization. Objective of the present stud was to study propose a standardized technique for LGP aiming at a better outcome. Setting. Settings: University-affiliated hospital. Methods: This is a retrospective analysis of patients who underwent LGP by the proposed technique., using seromuscular bites with non-absorbable thread, adoption of the four-bite technique, and calibration using bougie. Results: Eighty-eight consecutive morbidly obese patients had been operated by the proposed standardized technique of LGP between March 2010 and September 2014. There were 19 men and 69 women, with a mean age of 30.3 years and a mean BMI of 36.7kg/m2 (range 32-51kg/m2). The most frequently reported complication was prolonged early postoperative nausea/vomiting occurred in 5 of 88 (5.7%) patients. Weight regain was reported in one patient who was treated with conversion of LGP to laparoscopic mini-gastric bypass. Hospital stay was prolonged for a mean of 6.0 (3 -10 days). Postoperative follow-up period ranged from 2 to 38 months with a mean of 15 months. Percentage of excess weight loss was 38.2%, 52.0%, and 63.1% at 3, 6, and 12 months, respectively. Conclusions: The proposed technique of LGP would help in standardization of the procedure in order to improve the outcome; however, the clinical application of this proposed standardized technique should be tested by future studies.